Identifikasi Medication Error Pada Fase Dispensing Sediaan Aseptik Kemoterapi Di RSUP Fatmawati Periode Maret-April 2023 - Pangaribuan, Mutiara (Jurnal Farmasi Klinik Best Practice, 2023)
Medication error is an error in the use of drugs that has the potential to harm patient safety during the treatment process. Treatment with the parenteral route is more at risk of causing errors compared to other routes of administration because the drug goes directly to the blood vessels. The purpose of this study was to identify the incidence of medication error in the dispensing phase of chemotherapy aseptic preparations from March 15th to April 14th, 2023. This research method is observationally prospective with total sampling techniques based on chemotherapy protocols and drug storage forms observed for one month of work and data processing with descriptive analysis. There are 360 sample recipes that have been observed. The result of this study was that there was no identification of medication errors at the dispensing stage of aseptic chemotherapy preparations at Fatmawati Hospital. There was no medication error in the dispensing phase of chemotherapy aseptic preparations based on the type of incident and no medication error based on the risk grading matrix. Keywords: Medication error, dispensing, aseptic chemotherapy, RSUP Fatmawati